European Educational Principles of Forming Foreign Language Communicative Competence Among Students of Non- Linguistic University Faculties - Tetiana Soroka (Journal of Danubian Studies and Research, 2023)
A foreign language becomes an effective tool for achieving professional and personal goals, and a personal and activity-based approach in teaching helps to develop a student’s value attitude both to the process of learning a foreign language and to the results of own activities, minimizing the usual formal attitude to a foreign language as only a discipline included in the curriculum. The aim of the study is to investigate principles of forming foreign language communicative competence among students of non-linguistic university faculties adopted by the Council of Europe as Pan-European recommendations on language education. Taking into account the difference between the concepts of “competence” and “competency”, competencies are part of the whole, forming its unity and constituting the activity side of using a foreign language, and competence is a personal quality, including an emotional and value attitude to the actions performed. Actually, proficiency in a foreign language can be competence as a separately considered property of a person and competency as part of the general professional training of a future specialist. The components of competence are competencies that provide speech and non-speech activities of a language user. Competencies are formed and developed in the process of university studying.